Proposed upgrading of Restoran Puteri for Habsah Hassan and Rubiah Suparman at lot 3074 Jln Datuk Sulaiman, Sg Penchala 6000 Kuala Lumpur / Maesara Ismail - Ismail, Maesara (2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. As a accomplishing the final stage of learning process, a comprehensive design proposal needs to be prepare by each students. All the design must be related to the project that have been choose. Before doing the design, main aspect must be consider to get the information. So that, the research, case study, design schematic and the planning to make sure that client will give the good feedback with our design.